2017
DOI: 10.1007/s13197-017-2498-7
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic content and bactericidal effect of Mexican Citrus limetta and Citrus reticulata

Abstract: In this study, total phenolics, total flavonoids, hesperidin and ascorbic acid contents in bagasse, juice and seed of mexican sweet lime (Citrus limetta) and mandarine (Citrus reticulata) were determined at two commercial maturity stages (maturation index), as well as their bactericidal effect on Escherichia coli and Staphylococcus aureus. The results showed that bagasses had the highest total phenolics, total flavonoids, and hesperidin content for both, C. limetta, and C. reticulata; highest ascorbic acid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
0
5
1
1
Order By: Relevance
“…Further, the TPC extracted from SCB was higher than the 3.91 mg GAE/g obtained from B-type molasses ( 27 ) and the 3.751 mg GAE/g from molasses retrieved from sugar mills in Pakistan ( 28 ). Compared with other industrial byproducts, this study's SCB TPC was lower than the 0.38 mg/GAE extracted from Citrus limetta bagasse ( 29 ). It was also lower than the TPC extracted from six different white and red wine grape wastes, which showed TPC in a range of 32–59 mg GAE/g ( 30 ).…”
Section: Resultscontrasting
confidence: 58%
“…Further, the TPC extracted from SCB was higher than the 3.91 mg GAE/g obtained from B-type molasses ( 27 ) and the 3.751 mg GAE/g from molasses retrieved from sugar mills in Pakistan ( 28 ). Compared with other industrial byproducts, this study's SCB TPC was lower than the 0.38 mg/GAE extracted from Citrus limetta bagasse ( 29 ). It was also lower than the TPC extracted from six different white and red wine grape wastes, which showed TPC in a range of 32–59 mg GAE/g ( 30 ).…”
Section: Resultscontrasting
confidence: 58%
“…This study’s TPC from sugarcane bagasse is lower than the TPC extracted from Citrus limetta bagasse (20.38 mg GAE/g) [ 32 ]. It is also lower than the TPC extracted from six different white and red wine grape waste, valued within a range of 32 to 59 mg GAE/g [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because of its unique aroma and bioactive components content, lemon seed oil might be preferable for functional food, pharmaceutical and cosmetic applications [9,16]. Health-related properties of Citrus species include antiviral, anti-inflammatory, antimicrobial, hepatoprotective effects and many others [15,17,18,19,20]. Some studies have shown that the antioxidant and anti-inflammatory properties of Citrus flavonoids can be helpful against degenerative diseases, particularly brain diseases, as well as cardiovascular diseases and some types of cancer [3,6,18].…”
Section: Introductionmentioning
confidence: 99%